Management of Pneumonia - Febrina Aulia Natasya (Jurnal Medika Hutama, 2022)
Pneumonia is an acute infection or inflammation of the lung tissue caused by various microorganisms such as bacteria, viruses, parasites, fungi, exposure to chemicals, or physical damage to the lungs. Pneumonia can infect all age groups. Pneumonia can be divided into three types, namely community-acquired pneumonia (CAP), nosocomial pneumonia and ventilation-related pneumonia. Community-acquired pneumonia is the most common and can be fatal. The sources used in this paper include 28 articles obtained by doing a literature search on NCBI's PubMed and 2 books in the 2009-2020 publication range. Literature searching was carried out using the keywords septic pneumonia, therapy, epidemiology, and risk factors which were filtered with the provisions of the 2011-2021 publications. This literature search resulted in 1,971 articles which were then selected by 28 articles. Reading sources that have been collected are then analyzed using a systematic literature review method which includes activities for collecting, evaluating and developing research with a specific topic focus. The results of the literature review show that early detection and treatment of early and adequate antibiotics is one of the keys to reducing mortality in pneumonia cases. Empirical administration of antibiotics is recommended because it reduces mortality in some studies.